2001
DOI: 10.1046/j.1440-0960.2001.0463b.x
|View full text |Cite
|
Sign up to set email alerts
|

CONTINUING MEDICAL EDUCATION REVIEW Occupational skin disease in hairdressers

Abstract: Hairdressers belong to an occupational group that is commonly affected by occupational skin disease, specifically contact dermatitis, which may be allergic or irritant and, less commonly, contact urticaria. Occupational contact dermatitis predominantly affects apprentices, and atopy is a recognized risk factor associated with a poor prognosis. Repetitive wet work leading to irritant contact dermatitis, followed by exposure to allergens and the development of allergic contact dermatitis, are the main factors co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 52 publications
(122 reference statements)
3
34
0
4
Order By: Relevance
“…12 Contact dermatitis among hairdressers has multiple aetiological agents which include hair dyes, 3,12,13 gloves, 12,14 perming chemicals 12,13 and wet work. 4 The lower prevalence of hand dermatitis in this study may be due to the narrower range of hair chemicals available in Nigeria. Nail problems were prevalent in this study as in the Benin study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…12 Contact dermatitis among hairdressers has multiple aetiological agents which include hair dyes, 3,12,13 gloves, 12,14 perming chemicals 12,13 and wet work. 4 The lower prevalence of hand dermatitis in this study may be due to the narrower range of hair chemicals available in Nigeria. Nail problems were prevalent in this study as in the Benin study.…”
Section: Discussionmentioning
confidence: 69%
“…1 Occupational exposures to chemicals in the salon from hair sprays, dyes, hair relaxing creams and shampoos are well recognized. [2][3][4] Various health problems can occur as a result of these exposures. Studies from developed countries have focused on hand dermatitis 5,6 and respiratory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational skin diseases have significant implications both for individual (functionally, financially and psychosocially) and for the community at large 12) . Hairdressers are widely acknowledged as being at risk of dermatitis as a result of occupational exposure to a variety of chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study found that none of the hairdresser's salons surveyed in central and suburban areas of a large city had a ventilation system 12) . Improvements therefore need to be made to ventilation systems in hairdresser's salons, and health and safety measures aimed at lessening exposure need to be implemented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation